2017
DOI: 10.1007/164_2017_70
|View full text |Cite
|
Sign up to set email alerts
|

Evolutionary History of Voltage-Gated Sodium Channels

Abstract: Every cell within living organisms actively maintains an intracellular Na concentration that is 10-12 times lower than the extracellular concentration. The cells then utilize this transmembrane Na concentration gradient as a driving force to produce electrical signals, sometimes in the form of action potentials. The protein family comprising voltage-gated sodium channels (Nas) is essential for such signaling and enables cells to change their status in a regenerative manner and to rapidly communicate with one a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
22
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(23 citation statements)
references
References 106 publications
0
22
0
Order By: Relevance
“…The neuronal Nav channels localised within the T-tubules are predominantly associated with the β1 and β3-subunits [ 5 ]. These Nav α-subunits all lack a glycosylation site in their DI, S5-P extracellular loop, equivalent to Asn319 in Nav1.5 [ 9 ]. Hence, it is likely that the β1 and β3 Ig domains will bind onto these Nav α-subunits in a manner more like Nav1.7 than Nav1.5 ( Figure 4 A,B).…”
Section: The Nav Channel β-Subunits As Cell-adhesion Moleculesmentioning
confidence: 99%
See 1 more Smart Citation
“…The neuronal Nav channels localised within the T-tubules are predominantly associated with the β1 and β3-subunits [ 5 ]. These Nav α-subunits all lack a glycosylation site in their DI, S5-P extracellular loop, equivalent to Asn319 in Nav1.5 [ 9 ]. Hence, it is likely that the β1 and β3 Ig domains will bind onto these Nav α-subunits in a manner more like Nav1.7 than Nav1.5 ( Figure 4 A,B).…”
Section: The Nav Channel β-Subunits As Cell-adhesion Moleculesmentioning
confidence: 99%
“…The movement of the S4 helices in response to changes in membrane potential is transmitted to helices S5 and S6 of each domain. This leads to the transient opening and subsequent inactivation of the channel pore [ 8 , 9 ]. High-resolution structures obtained by cryogenic electron microscopy (cryo-EM), for the heart-specific Nav1.5 α-subunit, the skeletal muscle channel Nav1.4 and the neuronal channels Nav1.2 and Nav1.7 show that the four domains surround the central pore with four-fold pseudosymmetry.…”
Section: Introductionmentioning
confidence: 99%
“…Na + -dependent action potentials in placozoans could be mediated by two classes of voltage-gated cation channels (Ca v and Na v , Fig.3B ) with a shared topology containing 24 transmembrane (TM) helices, which are four repeats of 6TM domains[36,37,40,49,50] evolved from prokaryotic ancestors[37,51]. One sodium-conducting Ca v 3 and two Na v channels in Trichoplax have been reported[6,36,37,50].…”
Section: Resultsmentioning
confidence: 99%
“…Some medusozoans (Cnidaria) and bilaterians (including humans) independently developed Na v 1-type channels with very fast activation kinetics and high selectivity for Na + vs. Ca 2+ [6,36,37,40,49,54]. This metazoan-specific innovation is associated with the presence of a single positively-charged lysine (K) in the selective filter region, leading to DE K A and D K EA motifs for humans and jellyfishes, respectively[36,37,40,49,51]. In two species of Hoilungia (H4 and H13 haplotypes), we also identified lysine (K) but in the 4th vs. the 2nd positions (as in jellyfishes) of the second domain (DII, Fig.…”
Section: Discussionmentioning
confidence: 99%
“…We therefore focused on these, hoping to identify candidate effectors of ddN development and function. For instance, we detected an enrichment for transcripts from the Sodium voltage-gated channel subunit alpha a gene (Scna.a, KH.C9.462, LogFC = 1.6), encoding a voltage gated sodium channel orthologous to vertebrate NaV1 channels (Katsuyama et al, 2005;Nishino and Okamura, 2018;. By ISH, we found that Scna.a is upregulated specifically in the ddN and in MN1, but not in MGIN2 nor in any other MG neurons at around stage 23 (~15.5 hpf at 16°C), when most are differentiating (Fig 2E).…”
Section: Ddn-enriched Regulatorsmentioning
confidence: 99%